Application of Forage Processing Technology (Silage) for Animal Husbandry Communities - Harmoko; Alam, Asmirani; Fatimah Kamaruddin, Sitti; Leunupun, Engrith Grafelia; Suryaningrum, Sumarah; Rumtutuly, Fransheine; Lestari; Sangadji, Fauzan A (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Silage is a simple processed feed which is carried out by means of anaerobic fermentation. The community service activity program was done in Werwaru village in 2022. The main target in implementing this community service was the breeder community in Werwaru Village. This team consisted of lecturers and students of Pattimura University Animal Husbandry Study Program (PSDKU). The results of the implementation of community service with the theme of processing forage for animal feed into silage feed got well and smoothly, this could be said because of being participated on the head of villager and his staff. During the presentation on materials, the community gave interactive questions related to silage processing so that the breeder community felt more aware of the benefits, used and methods of processing forage into silage feed. With the implementation of this community service activity, it was hoped that it would provide benefits to the livestock community in Werwaru village.